Essentials of employee recruitment : individual and organizational perspectives - Slaughter, Jerel E.; Allen, David G. 1970- (Routledge, 2024)
"This book provides an insightful and comprehensive summary of the field of employee recruitment. Written from a scientific evidence-based perspective, and with contributions from global experts, it reviews the relevant research in the various areas of recruitment, considers the most pressing current issues in studying recruitment topics, and designs future research agendas for the field"-- Provided by publisher.
Keywords: Employees -- Recruiting.; Personnel management.; elektronické knihy; electronic books